Optimal. Leaf size=31 \[ e^{-x} \left (-3+2 x+\frac {x-x (5+x)+\log (2)}{x}-x \log (\log (x))\right ) \]
________________________________________________________________________________________
Rubi [F] time = 1.01, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {e^{-x} \left (-x^2+\left (8 x^2-x^3+(-1-x) \log (2)\right ) \log (x)+\left (-x^2+x^3\right ) \log (x) \log (\log (x))\right )}{x^2 \log (x)} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \left (\frac {e^{-x} \left (-x^2+8 x^2 \log (x)-x^3 \log (x)-\log (2) \log (x)-x \log (2) \log (x)\right )}{x^2 \log (x)}+e^{-x} (-1+x) \log (\log (x))\right ) \, dx\\ &=\int \frac {e^{-x} \left (-x^2+8 x^2 \log (x)-x^3 \log (x)-\log (2) \log (x)-x \log (2) \log (x)\right )}{x^2 \log (x)} \, dx+\int e^{-x} (-1+x) \log (\log (x)) \, dx\\ &=\int \left (\frac {e^{-x} \left (8 x^2-x^3-\log (2)-x \log (2)\right )}{x^2}-\frac {e^{-x}}{\log (x)}\right ) \, dx+\int \left (-e^{-x} \log (\log (x))+e^{-x} x \log (\log (x))\right ) \, dx\\ &=\int \frac {e^{-x} \left (8 x^2-x^3-\log (2)-x \log (2)\right )}{x^2} \, dx-\int \frac {e^{-x}}{\log (x)} \, dx-\int e^{-x} \log (\log (x)) \, dx+\int e^{-x} x \log (\log (x)) \, dx\\ &=\int \left (8 e^{-x}-e^{-x} x-\frac {e^{-x} \log (2)}{x^2}-\frac {e^{-x} \log (2)}{x}\right ) \, dx-\int \frac {e^{-x}}{\log (x)} \, dx-\int e^{-x} \log (\log (x)) \, dx+\int e^{-x} x \log (\log (x)) \, dx\\ &=8 \int e^{-x} \, dx-\log (2) \int \frac {e^{-x}}{x^2} \, dx-\log (2) \int \frac {e^{-x}}{x} \, dx-\int e^{-x} x \, dx-\int \frac {e^{-x}}{\log (x)} \, dx-\int e^{-x} \log (\log (x)) \, dx+\int e^{-x} x \log (\log (x)) \, dx\\ &=-8 e^{-x}+e^{-x} x+\frac {e^{-x} \log (2)}{x}-\text {Ei}(-x) \log (2)+\log (2) \int \frac {e^{-x}}{x} \, dx-\int e^{-x} \, dx-\int \frac {e^{-x}}{\log (x)} \, dx-\int e^{-x} \log (\log (x)) \, dx+\int e^{-x} x \log (\log (x)) \, dx\\ &=-7 e^{-x}+e^{-x} x+\frac {e^{-x} \log (2)}{x}-\int \frac {e^{-x}}{\log (x)} \, dx-\int e^{-x} \log (\log (x)) \, dx+\int e^{-x} x \log (\log (x)) \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.22, size = 27, normalized size = 0.87 \begin {gather*} e^{-x} \left (-7+x+\frac {\log (2)}{x}\right )-e^{-x} x \log (\log (x)) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.63, size = 32, normalized size = 1.03 \begin {gather*} -\frac {x^{2} e^{\left (-x\right )} \log \left (\log \relax (x)\right ) - {\left (x^{2} - 7 \, x + \log \relax (2)\right )} e^{\left (-x\right )}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.16, size = 41, normalized size = 1.32 \begin {gather*} -\frac {x^{2} e^{\left (-x\right )} \log \left (\log \relax (x)\right ) - x^{2} e^{\left (-x\right )} + 7 \, x e^{\left (-x\right )} - e^{\left (-x\right )} \log \relax (2)}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.03, size = 29, normalized size = 0.94
method | result | size |
risch | \(-x \,{\mathrm e}^{-x} \ln \left (\ln \relax (x )\right )+\frac {\left (x^{2}+\ln \relax (2)-7 x \right ) {\mathrm e}^{-x}}{x}\) | \(29\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [C] time = 0.40, size = 39, normalized size = 1.26 \begin {gather*} -x e^{\left (-x\right )} \log \left (\log \relax (x)\right ) + {\left (x + 1\right )} e^{\left (-x\right )} - {\rm Ei}\left (-x\right ) \log \relax (2) + \Gamma \left (-1, x\right ) \log \relax (2) - 8 \, e^{\left (-x\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 4.49, size = 28, normalized size = 0.90 \begin {gather*} \frac {{\mathrm {e}}^{-x}\,\left (x^2-7\,x+\ln \relax (2)\right )}{x}-x\,\ln \left (\ln \relax (x)\right )\,{\mathrm {e}}^{-x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.37, size = 22, normalized size = 0.71 \begin {gather*} \frac {\left (- x^{2} \log {\left (\log {\relax (x )} \right )} + x^{2} - 7 x + \log {\relax (2 )}\right ) e^{- x}}{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________